Teaching Trends in Ophthalmology - Divya Jain (Delhi Journal of Ophthalmology)
Medical education, including ophthalmology, has seen a paradigm shift with the introduction of competency-based medical education. The weightage has been shifted from a time-based curriculum to the acquisition of necessary skills and core competencies for the formation of a medical graduate.